MANAGEMENT INFORMATION SYSTEM DESIGN OF PRODUCTION AND SALES AT PT MANDIRI TEGUH INTI SEJAHTERA - Paskalia Kartini; Thommy Willay; Riri Supriani (SIMAK, 2022)
The change of a period is marked by the development of technology at that time. The development of technology, especially information technology, is related to the increasingly sophisticated computer technology used throughout the world. This makes the role of computers is very important in all aspects of human life. PT Mandiri Teguh Inti Sejahtera is a company that runs a pile production business. Data processing is still done manually such as on calculation process in determining raw materials for production. Sometimes errors in calculation can lead in to errors in production as well. Technique of analyzing and designing system is Unified Modelling Language (UML), database design uses Microsoft SQL Server 2008 and the application is designed using Microsoft Visual Basic.Net 2010. The results is Information System Design of production and sales, it can help PT Mandiri Teguh Inti Sejahtera to produce more precise and accurate information in data processing and decision making processes that are more effective and efficient.